Regulatory Transformation of House of Worship Construction to Realize Substantive Justice for Minority Groups - Thohir (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
The urgency of this policy analysis centers on the systematic barriers faced by minority groups in Frontier, Outermost, and Least Developed (3T) regions regarding the establishment of houses of worship, resulting from the rigid regulations of the Joint Ministerial Decree Numbers 9 and 8 of 2006. Administrative requirements mandating 90 users and 60 local supporters have become impossible thresholds to meet in sparsely populated areas, thereby triggering substantive injustice and structured licensing discrimination. This analysis employs a descriptive qualitative methodology through policy document studies and observations of regulatory implementation at the street-level bureaucracy, assessing policy alternatives using William N. Dunn’s evaluation criteria. The results and discussion indicate that the paradigm of administrative centralism has neglected the micro-demographic context of marginal regions, leading to the emergence of a